Corporate tax avoidance and ex ante equity cost of capital in Europe - Pulido, Matilde (2017)
The aim of this paper is to study the longstanding relationship between corporate tax avoidance and ex ante equity cost of capital in Europe, taking into consideration country specific characteristics, which are essential in a context of corporate tax competition. We find that investors apprehend tax avoidance differently at distinct levels of tax avoidance. We provide strong evidence that as low tax avoidance firms engage in greater tax avoidance, the ex ante equity cost of capital decreases. On the contrary, when high-tax avoidance firms undertake greater levels of tax avoidance, the ex ante equity cost of capital appears to increase. The benefits for firms engaged in lower tax avoidance are greater from 2008 onwards, during the period of financial crisis. These results confirm that in Europe a non-linear convex relationship exists between tax avoidance and ex ante equity cost of capital. Finally, we explore the impact of institutional characteristics and results suggest that in English common law countries the effect of corporate tax avoidance on ex ante equity cost of capital appears to be lower than that in other legal origins1